1996
DOI: 10.1021/bi952037f
|View full text |Cite
|
Sign up to set email alerts
|

Asp537 and Asp812 in Bacteriophage T7 RNA Polymerase as Metal Ion-Binding Sites Studied by EPR, Flow-Dialysis, and Transcription

Abstract: Asp537 and Asp812 are essential in the catalytic mechanism of T7 RNA polymerase. The mutants D537N and D812N have no detectable activity whereas the mutants D537E and D812E have significantly reduced activity relative to the wild-type. The hypothesis that these two amino acids act as metal-binding ligands has been tested using EPR with Mn2+ as the metal ion. Mn2+ is able to substitute for Mg2+ in transcription by T7 RNAP on templates containing the T7 promoter. Mg2+ and Mn2+ compete for binding sites, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 38 publications
2
41
1
Order By: Relevance
“…These motifs occupy similar positions in the various structures: motifs A and C, which contain invariant aspartates, lie in the palm. These aspartates coordinate catalytically essential Mg 2ϩ ions (43,44,59,66). Motif B, which contains an invariant lysine, lies in the fingers subdomain and makes up part of the enzyme's nucleotide binding pocket (27).…”
Section: Discussionmentioning
confidence: 99%
“…These motifs occupy similar positions in the various structures: motifs A and C, which contain invariant aspartates, lie in the palm. These aspartates coordinate catalytically essential Mg 2ϩ ions (43,44,59,66). Motif B, which contains an invariant lysine, lies in the fingers subdomain and makes up part of the enzyme's nucleotide binding pocket (27).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been reported that the use of Mn 2+ in place of Mg 2+ appears to result in polymerase activity compatible for a wider range of substrates for both RNA (Conrad et al 1995;Basu et al 1998) and DNA (Tabor and Richardson 1989) polymerases. Other studies suggest that Mn 2+ binds to polymerases with higher affinity, possibly involving two aspartic acid residues (Woody et al 1996;Martin et al 1999). Similar increases in binding affinity for the NTP substrates can reduce the apparent K m for the NTP substrates, which could result in tighter binding for an otherwise unfavorable NTP substrate.…”
Section: +mentioning
confidence: 99%
“…All important amino acid residues in the large C terminus of T7 RNAP were well conserved in phiL7 RNAP (see Fig. S4 in the supplemental material): Asp507 and Asp741 in phiL7 RNAP, corresponding to Asp537 and Asp812, respectively, in the active site of T7 RNAP; Lys577 and Tyr585 in phiL7 RNAP, corresponding to the catalytic residues Lys631 and Tyr811, respectively, in proximity to the active site of T7 RNAP; and His714 in phiL7 RNAP, corresponding to His784 of T7 RNAP, for holding short transcripts (34,53). However, the amino acid residues at the corresponding sites of major loops varied greatly in sequence and length (see Fig.…”
Section: Resultsmentioning
confidence: 99%